Relationship of cross-linguistics with other fields - Negmatova Marjona Islom qizi; Abduraxmanova Z.Y ("Conference on Universal Science Research 2023", 2023)
This article highlights the relationship, similarities and differences between hybrid linguistics and other disciplines. these aspects will be covered in detail in the following main sections